THE EFFECT OF DIGITAL STORYTELLINGTO IMPROVEUNIVERSITYSTUDENTS’ READING SKILS AND SELF EFFICACY - Fatin Nadifa Tarigan; Siti Aminah Hasibuan (Institut Pendidikan Tapanuli Selatan, 2021)
The innovative strategies and teaching media during the past few decades are always updating to increase the learners’ language skills especially literacy skill. Application of digital technology-based learning media is not only to maximize their language skills in both face-to-face and distance learning but also their interest and self- efficacy. The study aimed to find out whether the media digital storytelling significantly affects the students’ reading skill and self-efficacy. The study was conducted by experimental research with a quantitative approach. Fifty students of English Education Department at Universitas Pembinaan Masyarakat Indonesia participated in the study as the experimental (n=25) and the control (n=25). The data collection instrument was carried out by observation, questionnaires, and reading test. This study analysis method was descriptive statistics. The finding of the study revealed that digital media storytelling significantly affects the reading skills and self-efficacy of English Education Department students at Universitas Pembinaan Masyarakat Indonesia. By finding these suitable results, this media further can be applied to improve other language skills and also in other majors.